2020
DOI: 10.1101/2020.05.04.075051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The paraventricular thalamus provides a polysynaptic brake on limbic CRF neurons to sex-dependently blunt binge alcohol drinking and avoidance behavior

Abstract: Bed nucleus of the stria terminalis (BNST) neurons that synthesize and release the stress neuropeptide corticotropin-releasing factor (CRF) drive binge alcohol drinking and anxiety, behaviors that are primary risk factors for alcohol use disorder (AUD) and comorbid neuropsychiatric diseases more common in women than men. Here, we show that female C57BL/6J mice binge drink more than males and have greater basal BNST CRF neuron excitability and synaptic excitation. We identified a dense VGLUT2+ glutamatergic syn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…This is somewhat concordant with findings in BNST neurons expressing corticotrophin releasing factor (CRF), a subset of which express 5HT 2c (Marcinkiewcz et al, 2016). In these neurons, binge alcohol consumption significantly increases the proportion of male cells that are in a depolarization block such that they begin to resemble the proportions observed in females (Levine et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…This is somewhat concordant with findings in BNST neurons expressing corticotrophin releasing factor (CRF), a subset of which express 5HT 2c (Marcinkiewcz et al, 2016). In these neurons, binge alcohol consumption significantly increases the proportion of male cells that are in a depolarization block such that they begin to resemble the proportions observed in females (Levine et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…We found that although the mean sE/I amplitude and frequency in LHb neurons were not significantly different in mTBI and sham mice, mTBI resulted in significant shifts in cumulative probability curves of sE/I ratios (Figure 1 C-G, Kolmogorov-Smirnov tests, p<0.0001). Using the same data points for sEPSC and sIPSC amplitude and frequency, we also calculated and generated the mean, histogram, and cumulative probability curves of synaptic drive ratios in LHb neurons from sham and mTBI mice which incorporated all the properties of sEPSC and sIPSCs including amplitude, charge transfer and frequency 34 . While the mean synaptic drive ratios did not differ between sham and mTBI mice, mTBI resulted in a significant rightward shift in the cumulative probability curves of synaptic drive ratio suggesting that mTBI increased the overall excitatory synaptic drive onto LHb neurons (Figure 1H-I, Kolmogorov-Smirnov tests, p<0.0001).…”
Section: Results Mtbi Increased Spontaneous Lhb Tonic Activity and Ex...mentioning
confidence: 99%
“…While our findings highlight the use of in vivo calcium dynamics in BNST CRF neurons to understand pain, we acknowledge that the mechanisms contributing to sex-specific encoding remain to be determined. Recent evidence for sex-dependent excitatory transmission and synaptic facilitation in BNST CRF neurons suggests that highly active glutamatergic synapses in female mice prevent increases in excitatory tone that males are otherwise susceptible to 47 . Such differences in intrinsic excitability have major implications on how we interpret relative changes in calcium transients, since we measure these outputs by (i) normalizing pixels within each field-of-view (ΔF/F) and (ii) comparing nociceptive responses to baseline activity.…”
Section: Discussionmentioning
confidence: 99%